Evaluation of tricin, a stylet probing stimulant of brown planthopper, in infested and non‐infested rice plants. (16th September 2016) - Zhang, Z.; Cui, B.; Yan, S.; Li, Y.; Xiao, H.; Li, Y.; Zhang, Y.
Abstract: The flavone, tricin (5, 7, 4′‐trihydroxy‐3′, 5′‐dimethoxyflavone), is a valuable secondary metabolite that is common in gramineous plants, including cultivated rice ( Oryza sativa ). It can defend the rice plant against infestation by the brown planthopper (BPH), Nilaparvata lugens Stål, one of the most important pests of rice. This study evaluated the tricin concentration in infested and non‐infested rice plants. The results of the liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS) quantitative analysis showed that the tricin concentration in rice leaves was significantly higher than in the stems and roots. The mass concentration of tricin in the leaves at the leaf stage was significantly higher than at the tiller and booting stages. The relationship between rice variety, BPH resistance and tricin concentration was investigated. There was a significant negative correlation between tricin concentration and the injury severity scores for rice varieties. Moreover, BPH infestation caused variations in tricin concentration among rice plants. High BPH infestation levels can significantly reduce the tricin concentration in rice plants. However, there is no significant effect of the length of infestation times on tricin concentrations in rice leaves. These results suggest that there may be an elicitor in BPH saliva, which is injected into rice plants during BPH infestation and triggers the tricin metabolic system. Future studies need to identify the elicitor and clarify the mechanism underlying tricin reduction in infested rice plants.